Tata Kelola Kebijakan Sampah Plastik di Pemerintah Daerah Indonesia: Scoping Review - Afriyanni; Doni Hendrik (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2025)
Plastic waste issues in Indonesia continue to escalate in line with rapid urbanization, shifting consumption patterns, and weak waste governance capacity at the local government level. Although several national policy instruments have been introduced, therir implementation at the  locallevel remainss suboptimal. This study aims to examine how local governments formulate and implement plastic waste management policies, identify institutional, social, economic, and political factors influencing implementation outcomes, and explore the role of multi-stakeholder collaboration. A scoping review was conducted using the PRISMA-ScR protocol to assess 35 eligible studies published between 2015 to 2025 retrieved from Scopus and Google Scholar,. Thematic coding was applied to synthesize findings across research qustions. The results indicate that implementation remains constrained by fragmented institutional coordination, limited financing, weak enforcement mechanisms, and low public participation. However, effective practices are observed in localities that apply collaborative governance approaches, integrate informal waste actors, and adopt circular economy models. The study concludes that improving policy effectiveness requires harmonizing national–local regulatory frameworks, strengthening institutional capacity, and institutionalizing multi-stakeholder collaboration supported by incentives and monitoring systems. These findings provide a consolidated knowledge base to inform future policy design and implementation strategies for plastic waste governance in Indonesia.